ETOS KERJA TINGGI CERMIN KEPRIBADIAN MUSLIM UNGGUL - Tri Setyo (Kopertais Wilayah X Jawa Tengah, 2016)
AbstrakThe work ethic is one among global narrative that is now often discussed. This is because the work ethic is one of the critical success factors in the work. While high work ethic is strongly influenced by the personality, behavior and character of the person. Value of work in the view of Islam should be proportional to amaliyah mandatory, so mundane patterned positive work is also a religious duty. Islamic work ethic ushered characteristics are: (1) The intention sincere for Allah Alone, (2) Work Hard (al-Jiddu fi al-’amal), (3) Having high ideals (al-Himma al-’Aliyah) , With a work ethic that is being developed will affect the productivity of a person.Keywords: work ethic, Islam.